Ação declaratória de inexistência jurídica no âmbito do código de processo civil: meio idôneo de impugnação autônoma dos atos processuais juridicamente - Rezende, Lucas Ribeiro Vieira (2023)
This work proposes to research the main aspects of the declaratory action of inexistence of legal acts, also identified by some specialists as querela nullitatis or actio nullitatis, focusing on its hypotheses of application under the perspective of the Brazilian Code of Civil Procedure (Act #13,105 of March 16th, 2015). In order to address the core of the discussion, some reflections and the establishment of some conceptualizations and premises are necessary, such as the conceptualization and classification of actions and judgments, the minimum assumptions necessary for the constitution of the valid and regular development of the proceedings, in addition the analysis of the main aspects concerning the res judicata, and an examination regarding the system of breach of procedure. Next, this work analysis the declaratory action of inexistence of legal acts as an autonomous means to challenge acts that, from the perspective of the existence plane, are not capable of entering in the legal system, nor are under subject to the authority of res judicata, also approaching its controversial history, its main characteristics, and hypotheses of applicability from the current legal procedural order. In the end of the study, we present a synthesis and highlight the main ideas studied